Analisis Penerapan Permendagri 47/2021 Terhadap Aset Tetap Tanah, Peralatan dan Mesin di Kota Cimahi - Nur Fitri, Aryanti; Dwi Kusumastuti, Endah (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
This study aims to find out how BMD administration is implemented by BPKAD Kota Cimahi which includes bookkeeping, inventory, and reporting of BMD before and after Permendagri Number 47 of 2021 and the obstacles that occur. This study used a qualitativedescriptive method with data collection techniques using interviews, observation, and literature study. Data analysis techniques using data reduction, data presentation, and drawing conclusions. The results showed that the administration of BMD before the existence of Permendagri Number 47 of 2021 was carried out in accordance with Permendagri Number 19 of 2016 and Permendagri Number 17 of 2007. After the issuance of Permendagri Number 47 of 2021 the newly implemented BMD administration is an inventory of BMD, and the City of Cimahi is preparing an application E-MAD for BMD bookkeeping and reporting. Constraints faced are limited human resources and lack of competence, non-detailed product specifications, incomplete regulations and too many bookkeeping formats.